Optymalizacja płatności podatku VAT - Poszwa, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The characteristic feature of the Polish tax system evolution is the fact that tax constructions are becoming more and more complicated and the VAT meaning is rising in achieving the state budget. The Value Added Tax is acknowledged as a neutral one for running the business. However, we should say that VAT's neutrality is rather relative. The character of this tax (price increasing) and also shape of tax norms (recording and accounting duties) makes VAT to influence firm's decisions. It is also a source of additional risks for firms. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 123-133